Isolate Dependency of Brassica rapa Resistance QTLs to Botrytis cinerea - Zhang, Wei; Kwon, Soon-Tae; Chen, Fang; Kliebenstein, Daniel J. (Frontiers in Plant Science, 2016)
Generalist necrotrophic pathogens including Botrytis cinerea cause significant yield and financial losses on Brassica crops. However, there is little knowledge about the mechanisms underlying the complex interactions encoded by both host and pathogen genomes in this interaction. This potentially includes multiple layers of plant defense and pathogen virulence mechanisms that could complicate in breeding broad spectrum resistance within Brassica species. Glucosinolates are a diverse group of defense metabolites that play a key role in interaction between Brassica and biotic attackers. In this study, we utilized a collection of diverse B. cinerea isolates to investigate resistance within the B. rapa R500 x IMB211 recombinant inbred line population. We tested variation on lesion development and glucosinolate accumulation in parental lines and all population lines. We then mapped quantitative trait loci (QTL) for both resistances to B. cinerea and defense metabolites in this population. Phenotypic analysis and QTL mapping demonstrate that the genetic basis of resistance to B. cinerea in B. rapa is isolate specific and polygenic with transgressive segregation that both parents contribute resistance alleles. QTLs controlling defensive glucosinolates are highly dependent on pathogen infection. An overlap of two QTLs identified between resistance to B. cinerea and defense metabolites also showed isolate specific effects. This work suggests that directly searching for resistance loci may not be the best approach at improving resistance in B. rapa to necrotrophic pathogen.